Tin oxide / potassium sodium niobate composite material and preparation method and application thereof

The tin oxide/potassium sodium niobate composite material was prepared by hydrothermal method and calcined to form an integrated structure, which solved the problems of complexity and cost of methane gas detection equipment in the prior art, and achieved high selectivity and high sensitivity Sex detection effect.

CN118877937BActive Publication Date: 2025-02-07CHINA NAT PETROLEUM CORP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411281151.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-02-07
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The prior art methods for detecting methane gas are complex, large in size, and high in price, making them difficult to widely use.

Method used

The tin oxide/potassium sodium niobate composite material is prepared by hydrothermal method, and an integrated structure is formed through calcination treatment to improve the carrier mobility and energy band structure of the material, thereby improving the sensing characteristics of methane gas.

Benefits of technology

It realizes high selectivity and high sensitivity detection of methane gas, reduces equipment complexity and cost, and is suitable for a wide range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118877937B_ABST
    Figure CN118877937B_ABST
Patent Text Reader

Abstract

The present invention provides a tin oxide / potassium sodium niobate composite material and a preparation method and application thereof, belonging to the technical field of gas-sensitive materials. The preparation method of the tin oxide / potassium sodium niobate composite material comprises: using a tin source compound, a niobium source compound, a potassium source compound and a sodium source compound as raw materials, preparing a precursor by a hydrothermal method; calcining the precursor in air to obtain a tin oxide / potassium sodium niobate composite material. The method is simple to operate, has low equipment investment and low power consumption, and is suitable for mass production. In the composite material prepared by the method, a micron or nano heterojunction is formed between tin oxide and potassium sodium niobate, which is sensitive to methane gas, has good selectivity, can effectively capture methane gas, can be used as a methane gas-sensitive material, and is used to prepare a methane gas sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of gas-sensitive materials. Specifically, the present invention relates to a tin oxide / potassium sodium niobate composite material and a preparation method and application thereof; more specifically, the present invention relates to a tin oxide / potassium sodium niobate composite material and a preparation method thereof, a methane gas-sensitive material and a methane gas sensor. Background Art

[0002] Methane is an important carbon-based resource, which is widely found in many fields such as petroleum, coal mining, construction, and chemical industry. As people pay more attention to safety and environmental issues, the demand for methane gas detection is increasing day by day. Especially in the petrochemical industry, methane leaks may cause fires and explosions. Therefore, methane gas detection is widely used in the monitoring of oil wells, pipelines, oil storage tanks and other environments. Timely detection of methane leaks can protect people's lives and property.

[0003] Current methods for detecting methane include spectrophotometry, gas chromatography-mass spectrometry, and ion chromatography. However, the equipment used in the above methods is relatively complex, large in size, and expensive, making them difficult to be widely used. Summary of the invention

[0004] In view of this, in order to at least partially solve at least one of the above-mentioned technical problems, the present invention provides a tin oxide / potassium sodium niobate composite material and a preparation method and application thereof.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows.

[0006] According to an embodiment of one aspect of the present invention, a method for preparing a tin oxide / potassium sodium niobate composite material is provided, comprising: using a tin source compound, a niobium source compound, a potassium source compound and a sodium source compound as raw materials to prepare a precursor by a hydrothermal method; and calcining the precursor in air to obtain the tin oxide / potassium sodium niobate composite material.

[0007] According to an embodiment of another aspect of the present invention, a tin oxide / potassium sodium niobate composite material is provided, wherein tin oxide is continuously distributed inside the potassium sodium niobate so that a micron heterojunction or a nano heterojunction is formed between the tin oxide and the potassium sodium niobate, and the tin oxide / potassium sodium niobate composite material is prepared by the above-mentioned preparation method.

[0008] According to an embodiment of still another aspect of the present invention, there is provided a methane gas-sensitive material, comprising the above-mentioned tin oxide / potassium sodium niobate composite material.

[0009] According to an embodiment of yet another aspect of the present invention, a methane gas sensor is provided, comprising a gas sensitive element and the above-mentioned methane gas sensitive material coated on the outer surface of the gas sensitive element.

[0010] According to an embodiment of the present invention, during the hydrothermal reaction, the high temperature environment causes the solvent to be in a supercritical state exceeding its critical temperature and critical pressure, which is conducive to the full mixing of the hydrothermal reaction. In conjunction with the calcination treatment, the tin oxide and potassium sodium niobate are composited into an integrated structure, which promotes the grain growth of the composite material and improves the carrier mobility and band structure of the tin oxide / potassium sodium niobate composite material, which helps to improve the response speed of the composite material.

[0011] Potassium sodium niobate has no obvious redox properties at room temperature, but under heating conditions, the redox properties of potassium sodium niobate will be improved. When it comes into contact with oxygen-containing or reducing gases, a redox reaction will occur to produce oxygen vacancies. Oxygen vacancies, as active sites, can adsorb methane gas and react, providing more surface active sites for the adsorption of methane molecules, and improving the methane gas sensing properties of the composite material. At the same time, potassium and sodium ions exhibit alkaline properties. In the process of the tin oxide / potassium sodium niobate composite material contacting methane, potassium and sodium ions act as catalytic active centers to catalyze methane gas molecules to generate formate intermediates or carbonate intermediates. When the sensor works in a wide range of temperature modulation mode, methane is catalyzed by potassium sodium niobate to generate formate intermediates or carbon dioxide, so that the concentration of methane reaching the surface of tin oxide will change, and the concentration of the generated formate intermediates or carbonate intermediates will also change, and the two will be transferred together and adsorbed on tin oxide. Through the synergistic effect of potassium sodium niobate and tin oxide, high selectivity and sensitivity to methane gas are superimposed. A micron heterojunction or nano heterojunction is formed between tin oxide and potassium sodium niobate, which has a relatively stable structure, high mechanical strength, a wider resistance variation range, and shows high sensitivity to methane gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 A flow chart showing a method for preparing a tin oxide / potassium sodium niobate composite material according to an embodiment of the present invention is shown;

[0013] Figure 2 The scanning electron microscope image of the tin oxide / sodium potassium niobate composite material 1 of Example 1 of the present invention is shown;

[0014] Figure 3 A graph showing the change in response to methane over time in Example 1 of the present invention over a two-month period;

[0015] Figure 4 The scanning electron microscope image of the tin oxide / sodium potassium niobate composite material 2 of Example 2 of the present invention is shown;

[0016] Figure 5 shows the response curves of Examples 1 to 5 of the present invention to methane at different temperatures; and

[0017] Figure 6The bar graphs showing the responses of Examples 1 to 5 of the present invention to other gases at different temperatures are shown. DETAILED DESCRIPTION

[0018] Below, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of embodiments of the present invention. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of concepts of the present invention.

[0019] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.

[0020] In the case of using expressions such as "at least one of A, B, and C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, and C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, or C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.).

[0021] Methane is a flammable gas, usually the main component of natural gas, shale gas, combustible ice, etc., and is an important carbon-based resource. Especially in the petrochemical industry, methane leaks may cause fires and explosions. In related technologies, chemical resistance semiconductor gas sensors are used to detect methane. They use semiconductor materials as gas-sensitive materials, which makes it difficult to achieve high-sensitivity detection of methane, and the signal is easily interfered with, with poor selectivity, making it difficult to adapt to the detection needs of complex environments in the petrochemical field.

[0022] Tin oxide is an important wide bandgap n-type semiconductor material, which has three crystal forms, namely tetragonal, hexagonal and orthorhombic. In the process of realizing the concept of the present invention, it is found that the tetragonal tin oxide has a rutile structure, has the advantages of wide bandgap, low cost, strong conductivity, etc., but the selectivity and stability of the single phase of tin oxide are poor.

[0023] In order to solve the above problems, the surface activity of the tin oxide semiconductor is enhanced by modifying the tin oxide single-phase material, such as by doping or modification, so as to promote the adsorption of target gas molecules and thus enhance the gas sensitivity of the tin oxide semiconductor. However, in the process of doping or modification, it is found that it is difficult to significantly increase the sensitivity difference between different gas molecules using the above method, and it is difficult to achieve specific detection of the target gas, especially for the same type of gas molecules with similar properties, such as organic reducing gases.

[0024] Furthermore, in order to solve the above-mentioned problems, an attempt is made to compound the two materials so that the interface between the materials changes and the surface potential barrier of the composite material changes, which helps to improve the gas-sensitive properties of the composite material. In the process of screening the composite material, it was unexpectedly found that potassium sodium niobate can undergo redox reactions with reducing gases (mainly alkanes) under heating conditions, and the oxygen vacancies generated during the reaction can serve as active sites to further adsorb oxygen-containing or reducing gases and react. In the present invention, a tin source compound, a niobium source compound, a potassium source compound and a sodium source compound are mixed by a hydrothermal method to generate tin oxide and potassium sodium niobate, and the tin oxide and potassium sodium niobate are self-assembled during the reaction to form an ordered structure. Combined with calcination treatment, the uncrystallized tin oxide / potassium sodium niobate composite material has a stronger degree of crystallinity. When the tin oxide / potassium sodium niobate composite material responds to methane, the methane gas molecules preferentially pass through potassium sodium niobate. Under the catalytic action of potassium sodium niobate, the methane gas molecules are catalyzed to generate formate intermediates or carbonate intermediates. The concentration of methane after catalysis will change, and the concentration of the generated formate intermediates or carbonate intermediates will also change. The two are transferred to the tin oxide surface for adsorption, thereby superimposing to form a highly selective and highly sensitive characteristic signal belonging to methane gas.

[0025] Specifically, according to an embodiment of one aspect of the present invention, a method for preparing a tin oxide / potassium sodium niobate composite material is provided. Figure 1 The flowchart of the method for preparing the tin oxide / sodium potassium niobate composite material according to the embodiment of the present invention is shown. Figure 1 As shown, the method includes operations S101-S102.

[0026] In operation S101, a precursor is prepared by a hydrothermal method using a tin source compound, a niobium source compound, a potassium source compound and a sodium source compound as raw materials.

[0027] According to some embodiments of the present invention, during the hydrothermal reaction, the heating environment causes the solvent therein to be in a supercritical state. In the supercritical state, the solvent has a high solubility and diffusion rate, which is conducive to the full mixing and reaction of various reactants. Tin ions or atoms are very active in this environment and can react with the solvent in a heated environment to generate tin oxide. The niobium source acts as a reaction precursor, and in the presence of a potassium source and a sodium source, it reacts in a heated environment to generate the corresponding potassium sodium niobate. Tin oxide and potassium sodium niobate self-assemble during the hydrothermal reaction to form an ordered structure. Compared with other oxides, the tin oxide in the composite material has outstanding electron mobility and good electrical conductivity, which is more conducive to gas-sensitive response.

[0028] In operation S102, the precursor is calcined in air to obtain a tin oxide / potassium sodium niobate composite material.

[0029] According to some embodiments of the present invention, the calcination treatment makes the uncrystallized tin oxide-sodium potassium niobate microstructure have a stronger degree of crystallinity. Among them, the tin oxide with a smaller grain size will be evenly and continuously distributed inside the larger sodium potassium niobate during the reaction process, forming a continuous heterojunction layer, so that the tin oxide / sodium potassium niobate composite material presents an integrated structure as a whole. In the subsequent methane response, the methane gas molecules first pass through sodium potassium niobate and then reach the surface of tin oxide. The catalytic ability of the catalyst is related to the temperature, that is, when the temperature changes, the catalytic efficiency of the catalyst for the target reactant changes. Under the catalytic action of sodium potassium niobate, the methane gas molecules are catalyzed to generate formate intermediates or carbonate intermediates. The catalyzed methane and the formate intermediates or carbonate intermediates are transferred to the surface of tin oxide for adsorption, and the superposition forms a highly selective and highly sensitive characteristic signal belonging to methane gas, thereby achieving highly selective detection of methane.

[0030] Specifically, the reaction process for generating the formate intermediate is as follows:

[0031] .

[0032] The reaction process to generate carbonate intermediate is as follows:

[0033] .

[0034] According to some embodiments of the present invention, a precursor is prepared by a hydrothermal method and then calcined in air to obtain an integrated composite material of potassium sodium niobate coated with tin oxide, which can greatly improve its selectivity and sensitivity to methane gas, and the obtained tin oxide / potassium sodium niobate composite material has a large specific surface area and porosity, which increases the contact area between the composite material and methane gas, which is beneficial for the composite material to capture methane gas. After tin oxide and potassium sodium niobate (KNaNbO3) are combined, they can provide more surface active sites for methane gas adsorption, synergistically improve the methane gas sensing properties of the composite material, and can be used for highly selective detection of methane.

[0035] Specifically, operation S101 includes sub-operations S1011 to S1012.

[0036] In sub-operation S1011, the tin source compound, the niobium source compound, the potassium source compound and the sodium source compound are dissolved in a solvent and mixed to prepare a raw material mixed solution.

[0037] In one embodiment, sub-operation S1011 may include: dissolving a tin source compound in a first solvent to prepare a first solution. Dissolving a sodium source compound and a potassium source compound in a second solvent to prepare a second solution. Dissolving a niobium source compound in a third solvent to prepare a third solution. For example, the first solution and the third solution may be mixed first to prepare a first mixed solution; and then the second solution may be added to the first mixed solution to prepare a raw material mixed solution. The first solution and the second solution may also be mixed first to prepare a second mixed solution, and then the third solution may be added to the second mixed solution to prepare a raw material mixed solution. By dissolving the above compounds in solvents respectively, it helps to ensure uniform distribution of tin ions, niobium ions, potassium ions and sodium ions in the raw material mixed solution, which helps to regulate the uniform speed of the reaction and reduce the occurrence of side reactions when the precursor is prepared by a hydrothermal method later.

[0038] Specifically, the first solvent may be, for example, benzyl alcohol, the second solvent may be, for example, isopropanol, and the third solvent may be, for example, deionized water or anhydrous ethanol. When the first solvent is deionized water, the tin source compound is prone to hydrolysis reaction and directly generates tin oxide, but the reaction rate is relatively poor; when the first solvent uses benzyl alcohol, during the hydrothermal reaction, the tin source compound will first react with benzyl alcohol to generate an organic tin compound, and then further generate tin oxide, and the reaction is more complete. The use of the above solvents helps to make the dispersibility of the reactants better, improve the activity of the hydrothermal reaction, make the stability of the prepared precursor better, and help to regulate the particle size and morphology of the formed tin oxide and potassium sodium niobate.

[0039] According to some embodiments of the present invention, the tin source compound includes at least one of tin tetrachloride, tin dichloride, sodium stannate, and stannic acid, preferably tin tetrachloride. The niobium source compound includes niobium oxide. Further, the niobium oxide is niobium pentoxide, niobium dioxide, etc. The sodium source compound includes an alkaline compound of sodium. Further, the alkaline compound of sodium is one or more of sodium hydroxide, sodium bicarbonate, or sodium sulfate. The potassium source compound includes an alkaline compound of potassium. Further, the alkaline compound of potassium is one or more of potassium hydroxide, potassium bicarbonate, or potassium sulfate.

[0040] Taking tin tetrachloride as an example of a tin source compound, when tin oxide is prepared by a hydrothermal method, tin tetrachloride will undergo a partial hydrolysis reaction, partially generating tin oxide, and may also generate a second phase product, thereby affecting the stability and yield of tin oxide; when benzyl alcohol is used as the first solvent and isopropanol is used as the second solvent, it helps to make the dispersion of the reactants better and help to promote a more complete reaction for preparing tin oxide.

[0041] According to some embodiments of the present invention, in the tin oxide / sodium potassium niobate composite material, the molar ratio of the sum of potassium ions and sodium ions, tin ions, and niobium ions is (0.1-2):1:(0.1-2). When the proportion of tin ions is larger, the gas sensing performance of tin oxide is better and the response to gas is greater; as the proportion of sodium potassium niobate added increases, the response is gradually sacrificed and the mechanical stability is increased. It can be understood that the molar ratio of the sum of potassium ions and sodium ions, tin ions, and niobium ions includes but is not limited to 0.1:1:0.1, 0.2:1:0.2, 0.3:1:0.3, 0.4:1:0.4, 0.5:1:0.5, 0.6:1:0.6, 0.7:1:0.7, 0.8:1:0.8, 0.9:1:0.9, 1:1:1, 1.1:1:1.1, 1.2:1:1.2, 1.3:1:1.3, 1.4:1:1.4, 1.5:1:1.5, 1.6:1:1.6, 1.7:1:1.7, 1.8:1:1.8, 1.9:1:1.9, and 2:1:2.

[0042] Preferably, in the tin oxide / sodium potassium niobate composite material, the molar ratio of tin ions, potassium ions, sodium ions and niobium ions is 1:1:1:1. In the process of carrying out the relevant experiments of the present invention, it is found that when the molar ratio of the four is within the above range, the prepared tin oxide / sodium potassium niobate composite material has better mechanical stability while maintaining a higher response to gas.

[0043] In sub-operation S1012, the raw material mixed solution is prepared by a hydrothermal method to obtain a precursor.

[0044] In one embodiment, the raw material mixed solution is poured into a stainless steel reactor lined with polytetrachloroethylene, the filling degree is 70%, the seal is tightened, the reaction is carried out, and then the furnace is cooled to room temperature to obtain a suspension containing the reaction product. The inventors have found that the lower the temperature of the hydrothermal treatment and the shorter the time, the finer the generated material particles are, and the more conducive to gas sensitivity; the higher the temperature and the longer the time, the more complete the morphology of the material particles, the fewer broken or unformed particles, and the more conducive to sensing. Therefore, the reaction temperature of the hydrothermal method of the present invention is 140~180℃, and the reaction time is 2~6h. It helps to take into account the particle size, morphology and gas sensitivity of the formed material. The reaction temperature of the hydrothermal method can be, for example, 140℃, 150℃, 160℃, 170℃ or 180℃, etc., preferably 160℃. The reaction time of the hydrothermal method can be, for example, 2h, 3h, 4h, 5h or 6h, etc., preferably 5h.

[0045] In one embodiment, the suspension containing the reaction product is centrifuged to separate the supernatant from the precipitate by centrifugation to obtain a reaction product precipitate (i.e., a precursor, i.e., a product powder with a lower crystallinity), and the obtained precipitate is repeatedly washed with deionized water and anhydrous ethanol to remove the solvent or other impurities on the precipitate.

[0046] In one embodiment, before the precursor is calcined in air, the precursor is dried at a temperature of 60 to 80° C. and for a time of 12 to 20 hours. The drying process allows the precursor to be gradually dried and dispersed, which is beneficial to subsequent calcination and avoids agglomeration of material particles caused by direct calcination.

[0047] Specifically, the drying temperature may be, for example, 60°C, 65°C, 70°C, 75°C or 80°C, and the drying time may be, for example, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h.

[0048] According to some embodiments of the present invention, the precursor is calcined in air to obtain a tin oxide / sodium potassium niobate composite material. The higher the calcination temperature, the larger the material particles and the more stable the performance, but the gas response will be lower; the longer the calcination time, the larger the obtained material particles. Therefore, in one embodiment, the calcination temperature is 350°C to 550°C and the time is 2h to 4h, which helps to remove the residual organic matter in the precursor, so that the crystallinity and stability of the material can be taken into account. The calcination temperature can be, for example, 350°C, 400°C, 450°C, 500°C or 550°C, preferably 450°C. The calcination time can be, for example, 2h, 2.5h, 3h, 3.5h or 4h, preferably 3h.

[0049] The present invention also provides a tin oxide / potassium sodium niobate composite material, wherein the tin oxide is continuously distributed inside the potassium sodium niobate so that a micron heterojunction or a nano heterojunction is formed between the tin oxide and the potassium sodium niobate. The tin oxide / potassium sodium niobate composite material is prepared by the above-mentioned preparation method.

[0050] According to some embodiments of the present invention, tin oxide with relatively small grain size is evenly and continuously distributed inside potassium sodium niobate with larger grain size during calcination to form a continuous heterojunction layer, so that the tin oxide / potassium sodium niobate composite material presents an integrated structure as a whole, thereby improving the structural stability of the composite material and having higher mechanical strength.

[0051] According to some embodiments of the present invention, the tin oxide / sodium potassium niobate composite material has a coral-like stacking structure. The particles of the coral-like tin oxide / sodium potassium niobate composite material are micrometer-sized and have a relatively large number of pores, which can significantly increase the contact area between the composite material and the gas, making it more conducive to capturing the gas. The stacking structure of potassium sodium niobate coated with tin oxide helps to improve the gas sensitivity of tin oxide, and the combination of potassium sodium niobate and tin oxide helps to provide more surface active sites for gas molecule adsorption, synergistically improving the gas sensing properties of the composite material.

[0052] The present invention also provides a methane gas-sensitive material, comprising the above-mentioned tin oxide / potassium sodium niobate composite material.

[0053] According to some embodiments of the present invention, when the tin oxide / potassium sodium niobate composite material is applied to a methane gas-sensitive material, the methane gas molecules pass through potassium sodium niobate and reach the surface of the tin oxide. Under the catalytic action of potassium sodium niobate, the methane gas molecules are catalyzed to generate formate intermediates or carbonate intermediates, and the methane and formate intermediates or carbonate intermediates are transferred to the surface of the tin oxide for adsorption, superimposing to form a highly selective and highly sensitive characteristic signal of methane gas.

[0054] The present invention also provides a methane gas sensor, comprising a gas sensitive element and the above-mentioned methane gas sensitive material coated on the outer surface of the gas sensitive element.

[0055] According to some embodiments of the present invention, due to the use of a composite material formed by tin oxide and potassium sodium niobate, which has a specific integrated structure, the composite material is synergistically superimposed to form a high selectivity and high sensitivity characteristic signal belonging to methane gas, showing high sensitivity to methane; and showing lower sensitivity to most other gases, so that high selectivity to methane is presented during the response process, and the accuracy of the response is improved. And because potassium sodium niobate has a high catalytic activity, a high selectivity response can be obtained due to the superposition of the concentration changes of methane gas molecules, the concentration changes of formate intermediates, and the concentration changes of carbonate intermediates adsorbed on the surface of tin oxide, further improving the selectivity to methane gas.

[0056] The present invention also provides a method for preparing a methane gas sensor, comprising the following steps:

[0057] The above tin oxide / sodium potassium niobate composite material or the above methane gas sensitive material is coated on the gas sensitive element of the methane gas sensor.

[0058] In one embodiment, the gas sensing element is a sensor chip.

[0059] In one embodiment, a method for preparing a methane gas sensor comprises the following steps:

[0060] The tin oxide / sodium potassium niobate composite material is mixed with an organic slurry to prepare a gas sensitive slurry;

[0061] The slurry gas sensitive slurry is applied onto the gas sensitive element of the methane gas sensor.

[0062] In one embodiment, a method for preparing a methane gas sensor comprises the following steps:

[0063] The tin oxide / sodium potassium niobate composite material is placed in a ball mill, a ball milling medium and an organic slurry are added, and the gas sensitive slurry is obtained by ball milling;

[0064] The slurry is sprayed onto the gas sensitive element of the methane gas sensor by spraying.

[0065] In one embodiment, the organic slurry is: 30% ethanol, 20% terpineol, 30% deionized water, 10% hydroxypropyl methylcellulose, and 10% phthalate.

[0066] In one embodiment, the ball milling medium is agate balls, the ball milling time is 3 to 5 hours, preferably 4 hours, and the mass ratio of the tin oxide / sodium potassium niobate composite material to the organic slurry is 4:1.

[0067] The methane gas sensor manufactured by the present invention is based on a tin oxide / potassium sodium niobate composite material gas sensor and adopts a microstructure processing technology (MEMS technology, i.e., a microstructure processing technology from nanoscale to millimeter scale). The device has a small size, low cost, and low power consumption, is suitable for commercial and mass production, and has a wide market and application value.

[0068] The present invention is further described below by examples, drawings and related test experiments and results thereof. In the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present invention. However, it is obvious that one or more embodiments may also be implemented without these specific details. And, in the absence of conflict, the details in the following embodiments may be combined arbitrarily into other feasible embodiments.

[0069] It should be noted that the following specific examples are only for illustration, and the protection scope of the present invention is not limited thereto. The chemicals and raw materials used in the following examples are all commercially available or homemade by recognized processing methods.

[0070] Embodiment 1:

[0071] Preparation process of coral-like tin oxide / potassium sodium niobate composite material 1:

[0072] Weigh 0.05 mol of SnCl4 and add it to beaker 1 containing 15 mL of benzyl alcohol, and stir it magnetically to form a transparent solution; add 0.05 mol of KOH and 0.05 mol of NaOH to beaker 2 containing 15 mL of isopropanol, and stir it magnetically to form a clear and transparent solution; add 0.025 mol of Nb2O5 to beaker 3 containing 15 mL of deionized water, and stir it magnetically to form a turbid solution; add the solution in beaker 3 dropwise to beaker 1 until it is evenly mixed to form a pale white solution; add the clear solution in beaker 2 dropwise to the pale white solution until a uniform reaction product precipitation solution is obtained, and the dropping time is 20 minutes.

[0073] The reaction product precipitation solution was poured into a 100 mL stainless steel reactor with a polytetrachloroethylene liner, with a filling degree of 70%, and the reaction was sealed tightly; the reaction was hydrothermally reacted at 160°C in a drying oven for 4 hours, and then cooled to room temperature with the furnace to obtain a reaction product solution.

[0074] The reaction product solution was centrifuged to separate the supernatant from the precipitate to obtain the precipitate product at the bottom, and the precipitate product was washed three times with deionized water and anhydrous ethanol respectively. The washed precipitate product was placed in a constant temperature drying oven and dried at 80°C for 20 hours, and then naturally cooled to room temperature after drying.

[0075] The dried precipitated product was placed in a clean alumina ceramic crucible and then calcined in an air muffle furnace at 450°C for 3 hours to obtain a coral-like structured tin oxide / sodium potassium niobate composite material 1, which was stored in a brown sealed volumetric flask for subsequent analysis and detection.

[0076] Structural characterization of tin oxide / potassium sodium niobate composite material 1:

[0077] The morphology of the tin oxide / potassium sodium niobate composite material 1 was characterized by scanning electron microscopy (SEM, Model S-4800, Hitachi Co., Tokyo, Japan). Figure 2 FIG. 1 shows a scanning electron microscope image of the tin oxide / sodium potassium niobate composite material 1 of Example 1 of the present invention. Figure 2 It can be seen that SnO2 and KNaNbO3 are composited into an integrated structure, and the tin oxide / potassium sodium niobate composite material 1 as a whole presents a coral-like stacking structure.

[0078] Figure 3 The graph of the response of Example 1 of the present invention to methane over time within two months is shown. The fluctuation range of the response value is between 91-96, and the drift amplitude of the response value is about 5%, which is a relatively high standard in the gas sensor industry, which relies on the high stability of potassium sodium niobate. It can be seen that the composite structure of tin oxide and potassium sodium niobate not only has excellent sensitivity and selectivity, but also shows high long-term stability.

[0079] Embodiment 2:

[0080] Preparation process of coral-like tin oxide / potassium sodium niobate composite material 2:

[0081] The preparation process of Example 2 is substantially the same as that of Example 1, except that the addition amount of each raw material is changed, as follows:

[0082] Weigh 0.04 mol of SnCl4 and add it to beaker 1 containing 15 mL of benzyl alcohol, and stir it magnetically to form a transparent solution; add 0.05 mol of KOH and 0.05 mol of NaOH to beaker 2 containing 15 mL of isopropanol, and stir it magnetically to form a clear and transparent solution; add 0.025 mol of Nb2O5 to beaker 3 containing 15 mL of deionized water, and stir it magnetically to form a turbid solution; add the solution in beaker 3 dropwise to beaker 1 until it is evenly mixed to form a pale white solution; add the clear solution in beaker 2 dropwise to the pale white solution until a uniform reaction product precipitation solution is obtained, and the dropping time is 20 minutes.

[0083] The subsequent preparation method is the same as that of Example 1 to obtain a tin oxide / sodium potassium niobate composite material 2 having a coral-like structure, which is stored in a brown sealed volumetric flask for subsequent analysis and detection.

[0084] Structural characterization of tin oxide / potassium sodium niobate composite material 2:

[0085] The morphology of the tin oxide / potassium sodium niobate composite material 2 was characterized by scanning electron microscopy (SEM, Model S-4800, Hitachi Co., Tokyo, Japan). Figure 4 FIG. 2 shows a scanning electron microscope image of the tin oxide / sodium potassium niobate composite material 2 of Example 2 of the present invention. Figure 4 It can be seen that SnO2 and KNaNbO3 are composited into an integrated structure, and the tin oxide / potassium sodium niobate composite material 2 has a coral-like stacking structure as a whole.

[0086] Embodiment 3:

[0087] Preparation process of coral-like tin oxide / potassium sodium niobate composite material 3:

[0088] The preparation process of this embodiment 3 is basically the same as that of embodiment 1, except that the addition amount of each raw material is changed, as follows:

[0089] Weigh 0.04 mol of SnCl4 and add it to beaker 1 containing 15 mL of benzyl alcohol, stir it evenly with a magnetic force to form a transparent solution; add 0.075 mol of KOH and 0.075 mol of NaOH to beaker 2 containing 15 mL of isopropanol, stir it evenly with a magnetic force to form a clear and transparent solution; add 0.0325 mol of Nb2O5 to beaker 3 containing 15 mL of anhydrous ethanol solution, stir it evenly with a magnetic force to form a turbid solution; add the solution in beaker 3 dropwise to beaker 1 until it is evenly mixed to form a pale white solution; add the clear solution in beaker 2 dropwise to the pale white solution until a uniform reaction product precipitation solution is obtained, and the dropping time is 20 minutes;

[0090] The subsequent preparation method is the same as that of Example 1 to obtain a tin oxide / sodium potassium niobate composite material 3 having a coral-like structure, which is stored in a brown sealed volumetric flask for subsequent analysis and detection.

[0091] Embodiment 4:

[0092] Preparation process of coral-like tin oxide / potassium sodium niobate composite material 4:

[0093] The preparation process of Example 4 is substantially the same as that of Example 1, except that the temperature and time of the hydrothermal method are changed, as follows:

[0094] The reaction product precipitation solution was prepared in the same manner as in Example 1. The reaction product precipitation solution was poured into a 100 mL stainless steel reactor with a polytetrachloroethylene liner, with a filling degree of 70%, and the reaction was sealed; the reaction was carried out at 160° C. in a drying oven for 6 hours, and then cooled to room temperature with the furnace to obtain a reaction product solution. The subsequent preparation method was the same as in Example 1 to obtain a tin oxide / sodium potassium niobate composite material 4 with a coral-like structure, which was placed in a brown sealed volumetric flask for storage for subsequent analysis and detection.

[0095] Embodiment 5:

[0096] Preparation process of coral-like tin oxide / potassium sodium niobate composite material 5:

[0097] The preparation process of this embodiment 5 is basically the same as that of embodiment 1, except that the temperature and time of the calcination treatment are changed, as follows:

[0098] A precipitate product was prepared in the same manner as in Example 1 after drying and cooling to room temperature. The dried precipitate product was placed in a clean alumina ceramic crucible and then calcined in an air muffle furnace at 550° C. for 3 hours to obtain a coral-like structured tin oxide / sodium potassium niobate composite material 5, which was stored in a brown sealed volumetric flask for subsequent analysis and detection.

[0099] Comparative Example 1:

[0100] This comparative example 1 provides a preparation process of a tin oxide / copper cerium binary oxide composite material 1':

[0101] Weigh 0.04 mol of SnCl4 and add it to beaker 1 containing 15 mL of benzyl alcohol, and stir it magnetically to form a transparent solution; add 0.04 mol of Ce(NO3)3·6H2O and 0.04 mol of Cu(NO3)2·3H2O to beaker 2 containing 15 mL of deionized water, then add 0.031 g of urea and 3.125 mmol of polyvinylpyrrolidone k-30 (PVP) to beaker 2, and stir it magnetically to form a transparent solution; add the solution in beaker 1 dropwise to beaker 2 until it is mixed evenly to form a dark turbid solution; the dropping time is 20 minutes; then, transfer the mixed solution to a 100 mL autoclave and react at 160°C for 6 h. After the reaction, the obtained solid sample was immersed in a NaOCl solution (5000 ppm) for 2 h, then washed with anhydrous ethanol and deionized water three times each, dried and calcined at 500 °C for 2 h to obtain a tin oxide / copper cerium binary oxide composite material 1'.

[0102] Comparative Example 2:

[0103] This comparative example 2 provides a preparation process of a tin oxide / sodium niobate composite material 2':

[0104] Weigh 0.05 mol of SnCl4 and add it to beaker 1 containing 15 mL of benzyl alcohol, and stir it magnetically to form a transparent solution; add 0.05 mol of NaOH to beaker 2 containing 15 mL of isopropanol, and stir it magnetically to form a clear and transparent solution; add 0.025 mol of Nb2O5 to beaker 3 containing 15 mL of deionized water, and stir it magnetically to form a turbid solution; add the solution in beaker 3 dropwise to beaker 1 until it is evenly mixed to form a pale white solution; add the clear solution in beaker 2 dropwise to the pale white solution until a uniform reaction product precipitation solution is obtained, and the dropping time is 20 minutes.

[0105] The reaction product precipitation solution was poured into a 100 mL stainless steel reactor with a polytetrachloroethylene liner, with a filling degree of 70%, and the reaction was sealed tightly; the reaction was hydrothermally reacted at 160°C in a drying oven for 4 hours, and then cooled to room temperature with the furnace to obtain a reaction product solution.

[0106] The reaction product solution was centrifuged to separate the supernatant from the precipitate to obtain the precipitate product at the bottom, and the precipitate product was washed three times with deionized water and anhydrous ethanol respectively. The washed precipitate product was placed in a constant temperature drying oven and dried at 80°C for 20 hours, and then naturally cooled to room temperature after drying.

[0107] The dried precipitated product was placed in a clean alumina ceramic crucible and then calcined in an air muffle furnace at 450° C. for 3 hours to obtain a tin oxide / sodium niobate composite material 2′.

[0108] The methane gas sensing performance of the composite materials of Examples 1 to 5 and Comparative Examples 1 to 2 was tested:

[0109] The coral-like structured tin oxide / sodium potassium niobate composite materials 1 to tin oxide / sodium potassium niobate composite materials 5 prepared in Examples 1 to 5 and the tin oxide / sodium potassium niobate composite materials 1' to tin oxide / sodium potassium niobate composite materials 2' prepared in Comparative Examples 1 and 2 were made into gas sensors according to the following method, and the relevant gas sensing performance tests on methane were carried out:

[0110] The composite materials prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were placed in ball mills, respectively, and alcohol and dispersion were added for ball milling for 4 hours, followed by taking out and drying; the dried powder was placed in an agate mortar, and organic slurry (30% ethanol, 20% pineol, 30% deionized water, 10% hydroxypropyl methylcellulose, 10% phthalate) was added for manual grinding to achieve an appropriate viscosity, and then transferred to a ball mill and ball milled again for 4 hours to obtain each gas sensitive slurry.

[0111] By electrostatic micro-spraying, using a nozzle with a diameter of 140μm, each gas sensitive slurry was evenly sprayed on the sensitive electrode of the sensor, and then organic impurities were removed by sintering to obtain a gas sensor chip. The sensor chip was welded to the hardware driver module by gold wire ball welding, and placed on the aging table for aging for 20 hours to obtain the final required gas sensor 1~gas sensor 5 and gas sensor 1'~gas sensor 2'. The sensitivity test results to methane are shown in Table 1 below.

[0112] Table 1 Results of sensitivity test to methane

[0113]

[0114] The sensitivity test results of CO, H2, NO, formaldehyde, ethanol, benzene and ethylene at the optimal working temperature of methane 400℃ are shown in Table 2.

[0115] Table 2 Sensitivity test results to other typical gases at 400℃

[0116]

[0117] From the perspective of gas sensitivity, it can be seen from Tables 1 and 2 that Sn 4+ The higher the ratio, the better the overall sensitivity; when the solvothermal reaction temperature remains unchanged, the sensitivity decreases with the increase of time; when the sintering temperature remains unchanged, the longer the sintering time, the overall sensitivity decreases. Combined with the comparative examples, it can be seen that the sensitivity of the composite of tin oxide and potassium sodium niobate is much better than that of the composite with other semiconductor materials, mainly due to the catalytic performance of potassium sodium niobate on methane and the good synergistic effect with tin oxide. Figure 5 The response curves of Examples 1 to 5 of the present invention to methane at different temperatures are shown. Figure 6 The response bar graphs of Examples 1 to 5 of the present invention to other gases at different temperatures are shown. Figure 5 and Figure 6 It can be seen that in the range of working temperature of 100-400°C, the response of the sensor device gradually increases with the increase of working temperature, reaching the maximum value at 400°C, showing the typical response characteristics of semiconductor metal oxide gas sensors to methane. In addition, the responses of all embodiments to CO, H2, NO, formaldehyde, ethanol, benzene and ethylene at 400°C are much lower than those to methane, confirming the high selectivity to methane.

[0118] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a tin oxide / potassium sodium niobate composite material, characterized in that: include: A precursor is prepared by a hydrothermal method using a tin source compound, a niobium source compound, a potassium source compound and a sodium source compound as raw materials; calcining the precursor in air to obtain the tin oxide / sodium potassium niobate composite material; The reaction temperature of the hydrothermal method is 140~180℃; the reaction time is 2~6h; The calcination temperature is 350-550° C. and the calcination time is 2-4 hours.

2. The preparation method according to claim 1, characterized in that: The tin source compound comprises at least one of tin tetrachloride, tin dichloride, sodium stannate and stannic acid; The niobium source compound includes niobium oxide; The sodium source compound includes an alkaline compound of sodium; The potassium source compound includes an alkaline compound of potassium.

3. The preparation method according to claim 1 or 2, characterized in that: In the tin oxide / potassium sodium niobate composite material, the molar ratio of the sum of potassium ions and sodium ions, tin ions, and niobium ions is (0.1-2):1:(0.1-2).

4. The preparation method according to claim 1 or 2, characterized in that: In the tin oxide / sodium potassium niobate composite material, the molar ratio of tin ions, potassium ions, sodium ions and niobium ions is 1:1:1:

1.

5. The preparation method according to claim 1 or 2, characterized in that: Before the precursor is calcined in air, the precursor is dried; The temperature of the drying process is 60-80° C., and the time of the drying process is 12-20 hours.

6. A tin oxide / potassium sodium niobate composite material, characterized in that: Tin oxide is continuously distributed inside potassium sodium niobate, so that a continuous micron heterojunction or nano heterojunction integrated structure is formed between the tin oxide and potassium sodium niobate, wherein the tin oxide / potassium sodium niobate composite material is prepared by the preparation method of the tin oxide / potassium sodium niobate composite material according to any one of claims 1 to 5.

7. The tin oxide / potassium sodium niobate composite material according to claim 6, characterized in that: The tin oxide / potassium sodium niobate composite material has a coral-like stacking structure.

8. A methane gas-sensitive material, characterized in that: The methane gas sensitive material comprises the tin oxide / potassium sodium niobate composite material according to claim 6 or 7.

9. A methane gas sensor, characterized in that: The methane gas sensor comprises a gas sensitive element and the methane gas sensitive material according to claim 8 coated on the outer surface of the gas sensitive element.